2004
DOI: 10.1093/bioinformatics/bth167
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of metabolic network into functional modules based on the global connectivity structure of reaction graph

Abstract: http://genome.gbf.de/bioinformatics/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
119
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 27 publications
8
119
0
Order By: Relevance
“…3d), where the latter two modifications, when iterated, lead to positive and negative degree correlations, respectively [see 23, for an explanation of the corresponding algorithms]. In order to retain the modular structure of the network we identify modules with a path length algorithm similar to the one described in [38] and randomize solely links within or between single modules. Both modifications reveal an average entropy increase compared to the original metabolic networks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3d), where the latter two modifications, when iterated, lead to positive and negative degree correlations, respectively [see 23, for an explanation of the corresponding algorithms]. In order to retain the modular structure of the network we identify modules with a path length algorithm similar to the one described in [38] and randomize solely links within or between single modules. Both modifications reveal an average entropy increase compared to the original metabolic networks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding such structure feature may help to design more efficient network algorithms specifically for metabolic networks. For example, when designing an algorithm to decompose the metabolic network into modules [34] , we decomposed the GSC first and then expand the partition of GSC to other parts by a "majority rule" [24] . The sub-networks got from this algorithm exhibit a highly modularized bow-tie topological pattern similar to that of the global metabolic networks, while these small bow-ties are hierarchically nested into larger ones and collectively integrated into a large metabolic network.…”
Section: Spread Bow-tie Of Ecoli Metabolic Networkmentioning
confidence: 99%
“…They concluded that large-scale organizational frameworks such as the bow-tie are necessary starting points for higher-resolution modeling of complex biologic processes [23] . As the bow-tie structure of networks has drawn so much attention [15,[23][24][25][26] , clear visualization method of this architecture is being expected because of the large number of nodes and arcs, while GSC, the central part of bow-tie, deserves more detailed exploration. The decomposition of a network into k-cores [27] allows us to classify nodes simultaneously by both their connectivity and central placement in the network.…”
mentioning
confidence: 99%
“…Reaction graph: The nodes correspond to reactions. There is an edge between two reactions if a compound is both a product of one reaction and a substrate of the other one [14,19] . 3.…”
Section: Reconstruction Of Metabolic Network From Genome Informationmentioning
confidence: 99%